2008
DOI: 10.2516/ogst:2008017
|View full text |Cite
|
Sign up to set email alerts
|

Habitat of Biodegraded Heavy Oils: Industrial Implications

Abstract: Résumé -Habitat géologique des huiles lourdes biodégradées : implications industrielles -Les huiles lourdes, extra-lourdes et les sables bitumineux représentent des ressources mondiales équivalentes à celles des pétroles conventionnels. En raison de leur forte viscosité leur production est un défi technique et économique majeur. Comprendre l'origine et l'habitat géologique de ces pétroles non-conventionnels est un enjeu important pour optimiser les opérations d'exploration et de production. La grande majorité … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Biodegradation is controlled mainly by temperature, chemical composition of the oil and groundwater, and the relation between the oil volume and the oil-water contact area. Biodegradation affects petroleum fluid properties (lowers the API gravity and increases the in situ viscosity of the oil), alters the oil geochemistry, and increases the asphaltene content, sulfur content, acidity, and concentration of heavy metals in the oil Larter et al 2006;Eschard and Huc 2008). Gradients in oil composition and viscosity variations are common at reservoir scales both vertically and horizontally and are linked with proximity to active water (slow flux) and geochemical factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodegradation is controlled mainly by temperature, chemical composition of the oil and groundwater, and the relation between the oil volume and the oil-water contact area. Biodegradation affects petroleum fluid properties (lowers the API gravity and increases the in situ viscosity of the oil), alters the oil geochemistry, and increases the asphaltene content, sulfur content, acidity, and concentration of heavy metals in the oil Larter et al 2006;Eschard and Huc 2008). Gradients in oil composition and viscosity variations are common at reservoir scales both vertically and horizontally and are linked with proximity to active water (slow flux) and geochemical factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that these distribution functions can be (2) Z n = exp (A + BC n ) Fig. 16 A basin-tectonic context for naturally fractured carbonate heavy oil deposits [modified from Eschard and Huc (2008)] used to represent reservoir fluid compositions to at least C 19 (Pedersen et al 1984). The compositions of petroleum reservoir fluids are most often reported to C 7+ , C 10+ , or C 20+ and in rare cases to C 30+ (Katz and Firoozabadi 1978;Pedersen et al 1989).…”
Section: Appendix: Equations and Software Proceduresmentioning
confidence: 99%
“…Biodegradation in shallow reservoirs explains the origin of extraheavy oils and bitumen in Western Canada (Fig. 11) and Venezuela (Eschard and Huc 2008;Talwani 2002).…”
Section: Petroleum Migrationmentioning
confidence: 99%
“…Toward the Miocene, oil accumulations occurred in shallow reservoirs in the eastern and southwestern parts of the LBC, where the temperatures were less than 70°C. Under these conditions, biodegradation processes can take place, resulting in heavy oil reserves (Eschard & Huc ). This phenomena is currently taking place in the east, whereas in the west, the present‐day charge of hydrocarbons may consist of high API light oils that become mixed with previously degraded oils (Mora ; Moretti et al .…”
Section: Previous Studiesmentioning
confidence: 99%